Evolving Traditions: The Contemporary Dynamics of Uang Panai' in Bugis-Makassar Wedding Ceremonies - Masthurah, Nur; Amin, Fatimah Hidayahni; Sunusi, Seny Luhriyani; Hanafie, Nurharsya Khaer; Mohamad, Andi Riswan (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
The tradition of